On the design of bank revetments at inland waterways subjected to ship-induced water level drawdown: A probabilistic infinite slope analysis - Sorgatz, Julia; van den Eijnden, Abraham P.; Montenegro, Héctor; Hicks, Michael A. (Journal of Coastal and Hydraulic Structures, 2023)
To protect embankments along German inland waterways against local slope sliding failure caused by ship-induced water level drawdown, they are mainly secured by bank revetments. Often, large embankment sections are designed on the basis of a limited number of field and laboratory tests. Thus, uncertainties arise with regard to the mechanical and hydraulic ground properties. Current design standards account for these uncertainties by conservative design assumptions and empirical knowledge. This paper investigates the effects of vertically non-homogeneous ground properties on the required armour layer thickness using 1D random fields and an infinite slope model, which was modified to account for ship-induced drawdowns. Within the limitations of the infinite slope assumptions, the effects of a spatially variable friction angle and hydraulic conductivity are investigated and compared to deterministic benchmark cases. The investigations show that the level of safety obtained with the deterministic design depends strongly on the choice of the characteristic values. Particularly, the hydraulic conductivity determines the reliability of the design. In some cases, the 5 % quantile of the hydraulic conductivity does not yield a conservative estimate of the required armour layer thickness. In the case of the effective friction angle, the 5 % quantile may overestimate the required armour layer thickness for permeable soils. For less permeable soils, the 5 % quantile meets the solution of the random field analyses. For the combination of random effective friction angle and random hydraulic conductivity, all investigated benchmark studies seem to ensure engineering safety, but on different reliability levels. Based on these findings, recommendations regarding site exploration and choice of characteristic values of hydraulic conductivity and effective friction angle are provided.